Low cost, flexible, and distribution level universal grid analyser platform: designs and implementations. Issue 19 (20th May 2020) - Yin, He; Yao, Wenxuan; Zhan, Lingwei; Yu, Wenpeng; Zhao, Jiecheng; Liu, Yilu
Abstract : This study presents the designs and implementations of a distribution level open‐universal grid analyser (Open‐UGA) platform. The proposed Open‐UGA platform consists of distribution‐level phasor measurement units (PMUs), a standard signal generator, a router, and a server. Firstly, an overall introduction for the software, hardware, and server architectures of the Open‐UGA platform is given. To give a detailed design, the software, hardware, server block diagrams, flowcharts, and printed circuit board photo of the Open‐UGA platform are presented in detail. Then, four different types of distribution level PMU algorithms are introduced and implemented in the Open‐UGA platform to verify the flexibility and reconfigurability. The flowcharts and functionalities of these four UGAs with different PMU algorithms are given as example implementations. Finally, a performance comparison is conducted with both quantitative and illustrative results.